2021
DOI: 10.5041/rmmj.10443
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Proprotein Convertase Subtilisin/Kexin Type 9 Levels Predict Future Cardiovascular Event Risks in Hemodialyzed Black African Patients

Abstract: Context and Objective: Cardiovascular diseases are the leading cause of mortality in patients. In this context, proprotein convertase subtilisin/kexin type 9 (PCSK9) appears to be the new biomarker identified as interfering in lipid homeostasis. This study aimed to investigate the association between PCSK9, dyslipidemia, and future risk of cardiovascular events in a population of black Africans. Methods: A cross-sectional study was conducted between August 2016 and July 2020 in six hemodialysis centers in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…As reported, PCSK9 emerges as the new biomarker identified as interfering in lipid homeostasis. Raised serum PCSK9 levels have an association with higher TC and TG levels in Black African patients with HD 27 . Additionally, PCSK9 gene polymorphism functions in regulation of serum lipid levels, 28 and it is mainly associated with some serum lipid parameters in the Han population 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported, PCSK9 emerges as the new biomarker identified as interfering in lipid homeostasis. Raised serum PCSK9 levels have an association with higher TC and TG levels in Black African patients with HD 27 . Additionally, PCSK9 gene polymorphism functions in regulation of serum lipid levels, 28 and it is mainly associated with some serum lipid parameters in the Han population 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Raised serum PCSK9 levels have an association with higher TC and TG levels in Black African patients with HD. 27 Additionally, PCSK9 gene polymorphism functions in regulation of serum lipid levels, 28 and it is mainly associated with some serum lipid parameters in the Han population. 29 It is also reported that PCSK9 E670G polymorphism is linked to CAD risk under different genetic models.…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating whether PCSK9 concentrations are influenced by kidney function have mostly been small and revealed divergent results (8) (an overview is in Supplemental Table 1). The same holds true for PCSK9 concentrations and cardiovascular disease outcomes in patients with CKD (9 13) (Supplemental Table 2); most of the few studies conducted were either small and/or observed only a small number of cardiovascular disease events, which limits their conclusiveness.…”
Section: Introductionmentioning
confidence: 88%